The low pass rate in Geography at Ordinary Level in rural secondary schools: The case of Garikayi Secondary School in Silobela circuit in Kwekwe district. - Nyazenga, Esther Nyarai (Midlands State University, 2020)
This study sought to find out the factors that contribute to the low pass rate in Geography at O Level in rural secondary schools. A descriptive design was used as methodology. A sample of 6 teachers and 60 students was purposively sampled. Interviews were used to generate data while students responded to questionnaires. Content analysis was used to analyse the data generated to answer the two main questions of this study. This study revealed that the poor performance of students in Geography at Ordinary Level final examinations in rural secondary schools is attributed to their socio- economic circumstances which sometimes deny them proper role models who can motivate them to pursue education as a worthwhile investment. Most parents in rural areas have not gone far with education themselves. Rural secondary schools do not have adequate teaching and learning materials. There is need for a multi-sectoral approach to improve the pass rate in Geography in rural secondary schools. The government, the community, individual parents, the school system and students themselves should work hard to address the challenges to proper teaching and learning in these schools. Communities should inculcate in their children the true value of education. Schools should endeavor to provide adequate and relevant teaching and learning materials. Students themselves should take responsibility for their own future.